(untitled) (Economic and Political Thought, 2018)
The article shows that in the context of social security, every policy as well as every strategy will be a periodic concept of simultaneous thinking and acting in the field of achieving the assumed vision in the area of state security and its future. The above concept is identified as a unity of goals distinguished due to their social aspect, nature, scope and timespan of the implementation of the declared political intentions. It has been shown that such a course of action may be justified by the coercion of support, defence and protection of safe implementation of the common good. And it can also be evaluated as a remedy used for our survival.